The International Criminal Court and the responsibility to protect - Marinelli, Stefano (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2022)
This book examines the parallel development and interaction between the International Criminal Court (ICC) and the doctrine of the Responsibility to Protect (RtoP), assessing this relationship over time and through case studies of Darfur, Libya, and Syria. The similarities and connections between the doctrine and the Court have been highlighted by UN bodies, the organs of the Court, and scholars, yet their relationship and common impact on international law have been less explored. This book fills this gap in presenting an overview of how the development of RtoP and the ICC affect various branches of international law. The research shows that while the doctrine and the Court experienced significant implementation problems in their first decades of life, they nonetheless have the potential to contribute to the historical evolution of international law in combining their values of promoting international peace and protecting human rights. This interdisciplinary study will be useful for scholars of international law and international relations. It will also be beneficial to persons working for international organisations and for civil society organisations focused on the activity of the ICC and on the development of RtoP.
Keywords: LAW / General; LAW / Civil Rights; LAW / Courts; Responsibility to protect (International law); International Criminal Court; Just war doctrine; Humanitarian law; Human rights